2004
DOI: 10.7326/0003-4819-141-5-200409070-00101
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Review: Cardiac Resynchronization in Patients with Symptomatic Heart Failure

Abstract: In selected patients with heart failure, cardiac resynchronization therapy improves functional and hemodynamic status, reduces heart failure hospitalizations, and reduces all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
163
2
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(182 citation statements)
references
References 46 publications
6
163
2
11
Order By: Relevance
“…Regardless of being just a feasibility study, the modifications observed in the follow-up of patients submitted to left sympathetic blockade were similar to those documented with other well established approaches in the treatment of chronic heart failure [15][16][17] . Furthermore, as a phase I clinical trial, the current experience represents a conservative approach in the surgical achievement of a sympathetic blockade.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Regardless of being just a feasibility study, the modifications observed in the follow-up of patients submitted to left sympathetic blockade were similar to those documented with other well established approaches in the treatment of chronic heart failure [15][16][17] . Furthermore, as a phase I clinical trial, the current experience represents a conservative approach in the surgical achievement of a sympathetic blockade.…”
Section: Discussionmentioning
confidence: 62%
“…Similar to other palliative treatments of heart failure, mortality in the follow -up can occur by different complications [15][16][17] . The occurrence of two late deaths due to myocardial infarction or pulmonary thromboembolism in this series was probably related to the underlying disease and not to the procedure itself.…”
Section: Discussionmentioning
confidence: 99%
“…The first meta-analysis (99) showed that CRT reduced the number of deaths from progressive CHF by 51% and heart failure hospitalizations by 29%. In this metaanalysis, CRT was not associated with a significant reduction in all-cause mortality.…”
Section: Consensus Conference Recommendations On Heart Failure 2006mentioning
confidence: 99%
“…This ratio is much lower than the rate of reoperation reported in the literature in large multicenter studies. 1,21,22 Potential complications due to CS stent implantation may be the injury of the target vein and/or mechanical damage of the electrode. Our observations are in line with prior case reports that describe no complications during stent implantation into the venous system of the heart [23][24][25] or during stenting to fix the attained electrode position.…”
Section: Discussionmentioning
confidence: 99%